2023
DOI: 10.1080/09588221.2023.2173613
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of captioned videos for incidental vocabulary learning and retention: the role of working memory

Abstract: Working memory (WM) may be an essential component of incidental vocabulary learning and retention from captioned videos. However, how WM affects young learners' incidental vocabulary learning under different types of captions remains unclear. The present study employs a between-subject research design. The main purpose is to examine how two types of WM-phonological short-term memory and complex WM-impact vocabulary learning outcomes incidentally learned and retained from three types of captioning: (1) glossed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
7
2
Order By: Relevance
“…Teng (2022) investigated the impact of WM on incidental single word learning of young learners with limited VK levels from captioned videos of different types, finding that individual differences in phonological WM, measured through a nonword repetition task, positively predicted the learning of new words by young L2 learners in various captioning conditions. Surprisingly, the contribution of complex WM, assessed by the O‐span task, to incidental single word learning was not found to be statistically significant (see simarlar results in Teng 2023a). However, different results were detected in Teng (2023b).…”
Section: Literature Reviewmentioning
confidence: 93%
See 2 more Smart Citations
“…Teng (2022) investigated the impact of WM on incidental single word learning of young learners with limited VK levels from captioned videos of different types, finding that individual differences in phonological WM, measured through a nonword repetition task, positively predicted the learning of new words by young L2 learners in various captioning conditions. Surprisingly, the contribution of complex WM, assessed by the O‐span task, to incidental single word learning was not found to be statistically significant (see simarlar results in Teng 2023a). However, different results were detected in Teng (2023b).…”
Section: Literature Reviewmentioning
confidence: 93%
“…Additionally, phonological WM has been shown to be associated with the learning of new words by novice learners, particularly in contexts where learners deliberately attempt to commit new words to memory (e.g., Cheung, 1996;Speciale et al, 2004). However, there have been only a limited number of studies examining the role of WM in incidental vocabulary learning conditions (Montero Perez, 2020;Teng, 2023a). For instance, Montero Perez (2020) investigated the relationship between WM and incidental single word learning of higher-intermediate learners from audiovisual content without captions, finding that complex WM, measured through the O-span task, played a significant role in the learning of single words from such materials, while the impact of phonological WM, assessed by backward and forward digit span tasks, was not evident.…”
Section: Wm and Incidental Learning Of Single Words And Collocationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside rapid technological advances, learners who are learning English as a foreign language (EFL) now have more choices in using multimedia, a mixture of different media, such as text, video, audio, graphics and data, for vocabulary learning (Teng 2021). Multimedia, including multimedia glossing (Rassaei 2017;Ramezanali and Faez 2019), digital online reading (Teng 2018), and captioned videos (Teng 2019;Teng 2023), can help learners acquire both receptive and productive vocabulary knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…) (James & Galbraith, 1985) and the level of sensitivity to nonverbal cues within the multimodal input (Gardner, 1999) are believed to vary significantly between individuals. In the case of vocabulary learning, studies have found that both learners' pre-existing levels of vocabulary knowledge and complex working memory capacity (Montero-Perez, 2020) or phonological short-term memory capacity (Teng, 2023a) significantly correlated with learning gains from multimodal input. The evidence, however, has been mainly gathered in relation to incidental learning.…”
Section: Introductionmentioning
confidence: 99%